2010
DOI: 10.1073/pnas.1005911107
|View full text |Cite
|
Sign up to set email alerts
|

Distinct class of DNA-binding domains is exemplified by a master regulator of phenotypic switching in Candida albicans

Abstract: Among the most important classes of regulatory proteins are the sequence-specific DNA-binding proteins that control transcription through the occupancy of discrete DNA sequences within genomes. Currently, this class of proteins encompasses at least 37 distinct structural superfamilies and more than 100 distinct structural motifs. In this paper, we examine the transcriptional regulator Wor1, a master regulator of white-opaque switching in the human fungal pathogen Candida albicans. As assessed by a variety of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
105
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(114 citation statements)
references
References 32 publications
7
105
0
2
Order By: Relevance
“…These results can be well explained by the structural data as these nucleotides are recognized by WOPR via hydrophilic and hydrophobic interactions and most of the substitutions would either disrupt favorable interactions or cause unfavorable steric hindrances with the protein. The structural and biochemical data together indicate that the WOPR domain can recognize and bind a dsDNA containing the characteristic motif TAAACT with a strictly conserved T at position 1 and a highly conserved T at position 6 but some variations at the other positions with base preferences, which are largely in agreement with the biochemical results by Lohse et al [23]. This finding may explain why there are so many different CaWor1-binding sites (nearly 200 sites) in the C. albicans genome [15].…”
Section: Dna Core Motif Recognized By the Wopr Domainsupporting
confidence: 81%
See 4 more Smart Citations
“…These results can be well explained by the structural data as these nucleotides are recognized by WOPR via hydrophilic and hydrophobic interactions and most of the substitutions would either disrupt favorable interactions or cause unfavorable steric hindrances with the protein. The structural and biochemical data together indicate that the WOPR domain can recognize and bind a dsDNA containing the characteristic motif TAAACT with a strictly conserved T at position 1 and a highly conserved T at position 6 but some variations at the other positions with base preferences, which are largely in agreement with the biochemical results by Lohse et al [23]. This finding may explain why there are so many different CaWor1-binding sites (nearly 200 sites) in the C. albicans genome [15].…”
Section: Dna Core Motif Recognized By the Wopr Domainsupporting
confidence: 81%
“…Previous biochemical data showed that the N-terminal region of CaWor1 exhibits sequence-specific DNA-binding ability and can recognize and bind specifically to six different DNA sequences corresponding to the promoter regions of three genes [23]. To carry out the structural studies of CaWor1 in complex with its specific DNA, we first constructed the entire WOPR box of CaWor1 (residues 1-325) into the pET28a expression plasmid with the two CUG codons (residues Ser60 and Ser200) converted to UCG to compensate for the alternative genetic code in C. albicans [25] and expressed it in E. coli.…”
Section: Crystal Structure Of the Cawor1 Wopr-dsdna Complexmentioning
confidence: 99%
See 3 more Smart Citations